2001
DOI: 10.1016/s0896-6273(01)00482-2
|View full text |Cite
|
Sign up to set email alerts
|

A Visual Pigment Expressed in Both Rod and Cone Photoreceptors

Abstract: Rods and cones contain closely related but distinct G protein-coupled receptors, opsins, which have diverged to meet the differing requirements of night and day vision. Here, we provide evidence for an exception to that rule. Results from immunohistochemistry, spectrophotometry, and single-cell RT-PCR demonstrate that, in the tiger salamander, the green rods and blue-sensitive cones contain the same opsin. In contrast, the two cells express distinct G protein transducin alpha subunits: rod alpha transducin in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
95
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 97 publications
(105 citation statements)
references
References 57 publications
10
95
0
Order By: Relevance
“…In any case, the lack of increase in dark noise in transgenic S-opsin mouse rods indicates that the rate of thermal activation of A1 S-pigment in mouse is significantly lower than that of A2 L-pigment in amphibians. Concomitant with the low thermal activity of amphibian S-pigment (Rieke and Baylor, 2000), salamander S-cones are as sensitive to light as the corresponding rods (Perry and McNaughton, 1991;Ma et al, 2001), an observation consistent with spontaneous pigment activity playing a significant role in setting cone sensitivity under dark-adapted conditions. However, mammalian S-cones have a considerably lower sensitivity to light than mammalian rods (Nikonov et al, 2006), despite the apparently low thermal activity of mouse S-pigment found here.…”
Section: Discussionsupporting
confidence: 56%
“…In any case, the lack of increase in dark noise in transgenic S-opsin mouse rods indicates that the rate of thermal activation of A1 S-pigment in mouse is significantly lower than that of A2 L-pigment in amphibians. Concomitant with the low thermal activity of amphibian S-pigment (Rieke and Baylor, 2000), salamander S-cones are as sensitive to light as the corresponding rods (Perry and McNaughton, 1991;Ma et al, 2001), an observation consistent with spontaneous pigment activity playing a significant role in setting cone sensitivity under dark-adapted conditions. However, mammalian S-cones have a considerably lower sensitivity to light than mammalian rods (Nikonov et al, 2006), despite the apparently low thermal activity of mouse S-pigment found here.…”
Section: Discussionsupporting
confidence: 56%
“…The molecular mechanisms that control cell-fate choice among cone spectral subtypes in the zebrafish retina and the source of the patterning information are unknown. Finally, it is worth noting that we have never seen evidence of co-expression of multiple opsins in one cell, as has been reported in salamanders (Ma et al, 2001) and some mammals (Rohlich et al, 1994;Applebury et al, 2000;Lukats et al, 2002), although the relatively low sensitivity of the in situ hybridization technique would likely not have allowed us to detect very low levels of expression in the developing zebrafish cones. …”
supporting
confidence: 47%
“…Such heterologous expression of visual pigments is not, however, unknown. The blue sensitive cones and green rods of the tiger salamander both express the same SWS2 cone pigment (Ma et al 2001), thereby providing evidence that cone pigments can function with rod transducin, and the disparity in flash sensitivity could be attributed to a higher quantal photon catch by the larger rod outer segments. The converse situation proposed for the marsupial MWS cones expressing a rod pigment may be expected therefore to be fully functional and show a conelike sensitivity.…”
Section: Discussionmentioning
confidence: 89%